1987
DOI: 10.1111/j.1365-3059.1987.tb02274.x
|View full text |Cite
|
Sign up to set email alerts
|

Paclobutrazol and other plant growth‐retarding chemicals increase resistance of melon seedlings to fusarium wilt

Abstract: Studies were made of plant growth retardation and effects on resistanceof melon to fusarium wilt by soil application of paclobutrazol, other ergosterol biosynthesis inhibitors, the fungicide benomyl and the herbicide dinitramine. Paclobutrazol and ancymidol delayed the onset of wilting and were the most effective in reducing wilt incidence. A relationship between effectiveness in retarding seedling elongation and increasing resistance to fusarium wilt was observed. No chemical had a significant effect on patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 13 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…The mechanism of paclobutrazol in inducing tiller growth is interesting to be further evaluated. The dwarfism caused by paclobutrazol may also increase the resistance of plants towards waterlogging as well as pests and diseases attacks (Bridgemohan & Bridgemohan 2014;Cohen et al 1987). Figure 7 shows the average of chlorophyll content in 3 months old black rice plant.…”
Section: Average Of Plant Height and Tiller Numbersmentioning
confidence: 99%
“…The mechanism of paclobutrazol in inducing tiller growth is interesting to be further evaluated. The dwarfism caused by paclobutrazol may also increase the resistance of plants towards waterlogging as well as pests and diseases attacks (Bridgemohan & Bridgemohan 2014;Cohen et al 1987). Figure 7 shows the average of chlorophyll content in 3 months old black rice plant.…”
Section: Average Of Plant Height and Tiller Numbersmentioning
confidence: 99%
“…Studies undertaken so far have identified that, at the concentrations used to induce resistance, the herbicides or indole compounds have no apparent toxicity to the disease-causing organisms, suggesting that protection results from activation of indirect mechanisms (6,9,10,14,36,38). These mechanisms include physiological and anatomical changes (9), but in many cases are unknown (36).…”
mentioning
confidence: 99%
“…In addition, BAS 111..W treatment reduced the occurrence of light leaf spot induced by Pyrenopeziza brassicae (Stinchcombe et al 1986). Increased resistance to fungal infections have also been observed after application of the growth retardant ancymidol (Cohen et al 1987). Since BAS 111..W has no or only slight direct fungicidal properties, as observed against Alternaria spp.…”
Section: Resultsmentioning
confidence: 95%